Analisis Pengaruh Ability, Effort Dan Support Terhadap Kinerja Karyawan Toko Buku Gramedia Cabang Plaza Semanggi - R. A. R. A. Aryanti Wardaya Puspokusumo; Leonny Cathleen (Bina Nusantara University, 2011)
The purpose of the article is to analyze the influence of ability, effort and support towards employee performance in Plaza Semanggi branch of Gramedia bookstore. Method used in this research is the correlation of Pearson’s product-moment and double regression. The gathered data from questionnaire result provided uses likert scale and primary data from the company. The research result is to identify employees’ ability, effort, and support of organization having strong relationship and significant influence towards employees’ performance in Plaza Semanggi branch’s Gramedia bookstore. Hopefully, the organization’s ability, effort and support could be increased and became main factor in increasing employees’ performance. Besides, it is expected that the research result could give input for the company, especially in Plaza Semanggi branch, to increase the employee’s performance, which later will give positive impact for company development.